2009
DOI: 10.1111/j.1365-2427.2008.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aquatic insect emergence in response to whole‐lake experimental manipulations of introduced trout

Abstract: 1. Insects emerging from mountain lakes provide an important food source for many terrestrial predators. The amount of insect subsidy that emerges from lakes is influenced by predator composition, but predator effects could be ameliorated by greater habitat complexity. We conducted a replicated whole-lake experiment to test the effects of introduced fish predators on the abundance and composition of aquatic insects within and emerging from the littoral zone of 16 mountain lakes in the Trinity Alps Wilderness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…This discrete input of fish biomass can have major food web impacts through an instantaneous increase in the consumption required to support these newly stocked fish. For example, Pope et al (2009) found that trout stocked in alpine lakes altered the alpine lake ecosystem by preying on emerging insects that would otherwise be a terrestrial subsidy. SDBDMs could be used to more realistically explore the consequences of stocking timing and amount on prey dynamics in food web and ecosystem models.…”
Section: Discussionmentioning
confidence: 99%
“…This discrete input of fish biomass can have major food web impacts through an instantaneous increase in the consumption required to support these newly stocked fish. For example, Pope et al (2009) found that trout stocked in alpine lakes altered the alpine lake ecosystem by preying on emerging insects that would otherwise be a terrestrial subsidy. SDBDMs could be used to more realistically explore the consequences of stocking timing and amount on prey dynamics in food web and ecosystem models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to larger bodied taxa, the effects of introduced trout on smaller bodied Diptera are mixed. In the Sierra Nevada, the total abundance of dipteran larvae tends to be reduced in lakes with trout, an effect that is strongest at lower elevations (R.A. Knapp, unpublished data), and chironomids tended to emerge in greater numbers from lakes in the Klamath Mountains where fish were removed (Pope et al 2009). However, a study of high-elevation lakes in the southern Sierra Nevada found that mosquitos (Culex spp.)…”
Section: Aquatic Insectsmentioning
confidence: 99%
“…The larvae of most large-bodied aquatic insect taxa, including Odonata, Ephemeroptera, and Trichoptera, are negatively affected by trout in both the Sierra Nevada (Knapp et al 2001b and the Klamath (Pope et al 2009;Pope and Hannelly 2013) mountains. This translates into reductions in the biomass of aquatic insects emerging from trout-containing lakes (Finlay and Vredenburg 2007;Pope et al 2009;Epanchin et al 2010). Importantly, the effect of trout on insect abundance varies with elevation for some taxa.…”
Section: Aquatic Insectsmentioning
confidence: 99%
See 2 more Smart Citations